Inhibitors of class I histone deacetylases attenuate thioacetamide‐induced liver fibrosis in mice by suppressing hepatic type 2 inflammation. (17th August 2019) - Loh, Zhixuan; Fitzsimmons, Rebecca L.; Reid, Robert C.; Ramnath, Divya; Clouston, Andrew; Gupta, Praveer K.; Irvine, Katharine M.; Powell, Elizabeth E.; Schroder, Kate; Stow, Jennifer L.; Sweet, Matthew J.; Fairlie, David P.; et al.
Abstract : Background and Purpose: Chronic liver diseases feature excessive collagen and matrix protein deposition or crosslinking that characterises fibrosis, leads to scar tissue, and disrupts liver functions. There is no effective treatment. This study investigated whether treatment with selective histone deacetylase (HDAC) inhibitors might specifically reduce type 2 inflammation in the injured liver, thereby attenuating fibrogenesis in mice. Experimental Approach: Thioacetamide (TAA) was used to induce hepatic inflammation, fibrosis, and liver damage in female C57BL/6 mice, similar to the clinical features of chronic human liver disease. We used eight inhibitors of different human HDAC enzymes to probe histological (IHC and TUNEL), biochemical and immunological changes (flow cytometry, qPCR, Legendplex, andELISA ) in pathology, fibrosis, hepatic immune cell flux, and inflammatory cytokine expression. Key Results: Inhibitors of class I, but not class II, HDAC enzymes potently suppressed chronic hepatic inflammation and fibrosis in mice, attenuating accumulation and activation of IL‐33‐dependent, but not IL‐25‐dependent, group 2 innate lymphoid cells (ILC2) and inhibiting type 2 inflammation that drives hepatic stellate cells to secrete excessive collagen and matrix proteins. Conclusions and Implications: The results show that potent and selective inhibitors of class I only HDAC enzymes profoundly inhibit hepatocyte death and type 2 inflammation to prevent TAA‐induced liver fibrosis in mice. The specific HDAC enzymes identified here may be key promoters of inflammation in chronic liver fibrosis.